Conhecimento e acesso à informação sobre o papel da praia na proteção da costa - Aleixo, Juliana Silva (2019)
All around the world, coastal zones have a strong pull for human settlement, due to their attractive landscapes or economic prospects, making them the most populous places on the planet. Disregarding, or even ignoring, the natural characteristics this type of environment, the anthropic occupation, in many occasions, occurs in a disorderly and improper manner. The inhabitants of these zones are thus susceptible to the constant morphodynamic variations of these environments. In many countries, the establishment of a range of protection or restrictions are adopted in order to prevent losses and damages caused by coastal erosion, as well as to avoid changing the landscape characteristic of such places. In Brazil, the National Coastal Management Plan (Projeto Orla) seeks to discipline the use and occupation of the seashore spaces and resources, directing public power and society to define and decide what should properly be done in this space. The present work had as objective to make a document on coastal processes necessary for the understanding and participation of the civil community in the implementation of the Projeto Orla and/or the critical participation of the citizen on the actions taken in beaches and coasts. Though interviews with beach users have shown that this public has some level of correct understanding of the beach environment, it has become clear that there are important knowledge gaps regarding the coastal area that needed further education, the understanding that the beach can protect the shore in case of a possible rise in sea level is one of them. The information available at the Internet on the dynamics of the coastal area and particularly about beach processes revealed that, excluding more technical approaches, the material disponible is generally insufficient or superficial and does not clarifies the natural processes of the coastal zone, nor the relation between beach resilience, climate change and coastal vulnerability. It was noted that the level of information provided by the media in general does not allow such a conclusion to be reached, thus proven to be insufficient. Therefore, it was presented in this work, the disclosure of this information in an appropriate way and with vocabulary accessible to the ordinary citizen through material available in print media (booklet) and by the web (blog) enabling any common citizen to initiate the subject and the possibility of to critically discuss specific actions for the martime edge.